Multiple Looks of Auditory Empty Durations Both Improve and Impair Temporal Sensitivity - Kuroda, Tsuyoshi; Yoshioka, Daiki; Ueda, Tomoya; Miyazaki, Makoto (Frontiers in Human Neuroscience, 2018)
Discrimination of two neighboring empty durations that are marked by three successive sounds is improved when the presentation of the first (standard, S) duration is repeated before that of the second (comparison, C), as SSSSC. This improvement in sensitivity, called the multiple-look effect, has been explained by a statistical model regarding variability. This model assumes that the perceived duration of the standard is averaged across observations (within a trial within an individual). The increasing of the number of observations thus reduces the standard error of the mean perceived duration. Alternatively, the multiple-look effect is attributed to the listener’s prediction based on regular rhythm. Listeners perceive regular rhythm during the repetition of the standard, predict the timing of subsequent sounds, and detect a sound that is displaced from the predicted timing. These models were tested in the present experiment in which the main factor was a temporal separation between the standard and the comparison; i.e., these durations were adjacent to each other as SSSSC or separated by a temporal blank as SSSS_C. The results differed between stimulus structures. First, the multiple-look effect was replicated in the SSSSC condition (yielding a higher performance than SC), but disappeared in SSSS_C (having no difference with S_C). Second, no multiple-look effect occurred in CSSSS (no difference with CS), and moreover, an impairment effect was observed in C_SSSS (a lower performance than C_S). Finally, discrimination was improved in SSSS_CCCC compared with SSSSCCCC, the effect being kept even when sounds were aligned at irregular intervals. These findings are not consistent with those expected from the statistical model because the temporal separation should have no effects if the number of standards had been a sole parameter determining the multiple-look effect. The prediction-based model can explain the first finding; inserting a blank between the standard and the comparison violates the listener’s prediction based on regular rhythm, thus reducing the multiple-look effect. However, it did not expect the other findings and required revisions. Notably, the second finding indicates that the formation of regular rhythm can impair temporal discrimination. In other words, an inversed multiple-look effect occurs.